Rancang Bangun Alat Bantu Fiksasi Pemeriksaan Radiografi Lumbal Oblik - Prastanti, Agustina Dwi; Sulistiyadi, Haris; Fatmayanti, Halinda (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: The oblique lumbar examination has been carried out. The position of object isn't object angle at 45Â° to the image receptor, but only estimate it. It caused not optimal image of scottie dog sign and spondylolysis (pressure in pars interarticularis). Therefore, an examination aid is needed to make it easier to obtain the position of the oblique lumbar object.Methods: This research design is a RnD study with the ADDIE model which is carried out with five stages, namely analysis, design, development, implementation, and evaluation. The data is carried out by observing, designing, testing, and analyzing whether there are artifacts.Results: An oblique lumbar radiographic examination fixation aid was produced from acrylic material with a thickness of 5 mm. Acrylic is shaped like a right-angled triangular prism building which has a longer base measuring 50 cm, width 42 cm, and height 25 cm. A rectangular base with a length of 50 cm is pressed against the patient's body so that the supporting part of the angled triangle that supports the patient's lumbar region or the patient's body does not shift during an oblique lumbar radiography examination. This tool has a mass dimension of 2.5kg.Conclusion: The design of the oblique lumbar radiographic examination fixation tool resembles a right-angled triangular prism with one side tilted at a 45 degree angle to adjust the position of the object so that it can obtain a good view of the Scottie dog sign to show part of the pars interarticularis.